Pengaruh Kompensasi Gaji, Motivasi dan Rekrutmen Terhadap Kinerja Karyawan (Studi Kasus PT Surya Pertiwi, Tbk) - Miken yulita (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
This study aims to determine the effect of salary compensation, motivation, and recruitment variables on employee performance at PT. Surya Pertiwi, Tbk. The method used in this research is descriptive method and multiple regression analysis. The research was conducted by distributing questionnaires to 100 respondents who work at PT. Surya Pertiwi, Tbk. The results of the study show that compensation and work motivation have a positive and significant effect on employee performance. Further discussion regarding the research results can be seen in this study.